Effect of Organizational Ethics in Banking Industry in Bangladesh - Dewan Asphia, Nowrin; Srivastava, Mohit; Martínez, Felipe; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
Economic performance of a country is largely determined by banking and financial system. This sector plays a vital and crucial role in the farming of different policies in today's environment. Ethical issues in the financial sector affect the overall banking industry and its performance in Bangladesh. This study is conducted to find out the relationship between the factors which directly or indirectly influence the business ethical practice. Data were derived from a questionnaire, explicitly focused on the Banking sector of Bangladesh. The result showed that the overall bank performance is highly influenced if there is a practice of business ethics which depends on the content of code of conduct. The details are discussed in the paper.
Vedoucí práce: Mohit Srivastava
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses